2021
DOI: 10.1371/journal.pone.0245530
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of integrating canine olfaction with chemical and microbial profiling of urine to detect lethal prostate cancer

Abstract: Prostate cancer is the second leading cause of cancer death in men in the developed world. A more sensitive and specific detection strategy for lethal prostate cancer beyond serum prostate specific antigen (PSA) population screening is urgently needed. Diagnosis by canine olfaction, using dogs trained to detect cancer by smell, has been shown to be both specific and sensitive. While dogs themselves are impractical as scalable diagnostic sensors, machine olfaction for cancer detection is testable. However, stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 42 publications
(36 reference statements)
2
29
0
1
Order By: Relevance
“…No exclusion criteria regarding medical history, hormonal status, diet, clinical treatments, or tobacco consumption were considered for the selection of participants. Although some of these could be hypothesized as confounding factors for the olfactory discrimination, previous researches ( Biehl et al., 2019 ; Guest et al., 2021 ; Kokocińska-Kusiak et al., 2021 ; Mazzola et al., 2020 ) demonstrated that, if well-standardized protocols are involved for recruitment, conservation of urine samples and analysis, they do not affect the classification performance.…”
Section: Methodsmentioning
confidence: 99%
“…No exclusion criteria regarding medical history, hormonal status, diet, clinical treatments, or tobacco consumption were considered for the selection of participants. Although some of these could be hypothesized as confounding factors for the olfactory discrimination, previous researches ( Biehl et al., 2019 ; Guest et al., 2021 ; Kokocińska-Kusiak et al., 2021 ; Mazzola et al., 2020 ) demonstrated that, if well-standardized protocols are involved for recruitment, conservation of urine samples and analysis, they do not affect the classification performance.…”
Section: Methodsmentioning
confidence: 99%
“…More and more evidence revealed that VOCs might be the dangerous factors influencing public health. Although some studies reveal that urinary volatiles and chemical characteristics may help detect prostate changes in a non-invasive way (60)(61)(62), the association between environmental VOCs exposure and PSA concentrations has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Weetjens et al, (2009) reported that African giant-pouched rats (Crietomys gambianus) were successfully trained to identify Mycobacterium tuberculosis in sputa of patients suspected of having tuberculosis, with a sensitivity of 89.1% and specificity of 80.1%. The use of sniffer dogs has a long history and a wider variety of applications, including the detection of explosives or land mines, the detection of drugs or the search of missing peoples, health-threatening microbial contaminations in hospitals and apartments (Fischer-Tenhagen et al, 2013;Fischer-Tenhagen et al, 2017;Else, 2020;Grandjean et al, 2020;Mazzola et al, 2020;Guest et al, 2021). Dogs are thought to poses an extremely keen sense of smell that is reported to be 10000 to 100000 times more accurate than in humans (Rygg et al, 2017;Else, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported thresholds ranging from parts-per-million to part-for-trillion (Leitch et al, 2013). It has also been reported that highly trained dogs can accurately detect distinctive odors, also named volatile organic compounds (VOCs) that are present in urine of men with prostate cancer as products of cell metabolism (Willis et al, 2004;Gordon et al, 2008;Cornu et al, 2011;Jobu et al, 2012;Leitch et al, 2013;Taverna et al, 2015;Taverna et al, 2016;Guest et al, 2021). As dogs can reliably detect these compounds, it follows that they could also be used to test scent control products, such as a fabric stoma pouch cover.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation